2019
DOI: 10.3986/ags.2250
|View full text |Cite
|
Sign up to set email alerts
|

Floods types in a mountain catchment: The Ochotnica River, Poland

Abstract: Annual subscription/letna naročnina: 20 € for individuals/za posameznike, 28 € for institutions/za ustanove. Single issue/cena posamezne številke: 12,50 € for individuals/za posameznike, 16 € for institutions/za ustanove. Cartography/kartografija: Geografski inštitut Antona Melika ZRC SAZU Translations/prevodi: DEKS, d. o. o. DTP/prelom: SYNCOMP, d. o. o. Printed by/tiskarna: Tiskarna Present, d. o. o. Print run/naklada: 350 copies/izvodov The journal is subsidized by the Slovenian Research Agency and is issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(31 reference statements)
0
7
0
1
Order By: Relevance
“…Average number of floods was 10.5 per year. This value is higher than the average recorded in the basin of the Ochotnica stream in Gorce Mountain [10]. The floods duration amounted to 14239 hours, representing 3.6% of the duration of the discussed period (Table 1).…”
Section: Resultsmentioning
confidence: 63%
“…Average number of floods was 10.5 per year. This value is higher than the average recorded in the basin of the Ochotnica stream in Gorce Mountain [10]. The floods duration amounted to 14239 hours, representing 3.6% of the duration of the discussed period (Table 1).…”
Section: Resultsmentioning
confidence: 63%
“…The first covers the period from 1972 to 1996, when aggradation (3.9 cm year -1 ) was the predominant process, whereas from 1997 to 2011 incision (3.2 cm year -1 ) dominated. It should be noted that despite the change in the trend of the level of the Ochotnica channel, there were no statistically significant changes in the floods frequency in the analyzed period [8]. Discharge analysis confirmed incision of the Ochotnica channel.…”
Section: Dynamics Of River Channelsmentioning
confidence: 69%
“…This example showed that the same water level in the multiyear period corresponded to higher discharges, which was evidence of the river channel incision. The periods of the channel referred to the period of the centrally planned economy with a large share of cultivated land and incision referred to free market economy with a rapid decrease of arable land in Gorce catchments [8], [18]. The trend of the incision of the Ochotnica channel in recent years was compatible with the changes of the river channels level noted in the Beskidy Mountains [19].…”
Section: Dynamics Of River Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recent decades at the Ochotnica valley, two periods of channel development was discovered. Between 1976 and 1996, aggradation was the predominant process, whereas from 1997 to 2011, incision dominated (Kijowska-Strugała & Bucała-Hrabia, 2019). Krzemień (1984), as the first, was drawing attention to the domination of deep erosion in streams on northern slopes of the Gorce Mts.…”
Section: Fluvial Processes and Landformsmentioning
confidence: 99%